Validity of an Accelerometer Used to Measure Step Count in Children With Idiopathic Toe Walking. Issue 2 (April 2017) - Christensen, Catie; Haddad, Amanda; Maus, Elizabeth
Abstract : Purpose: To assess the validity of accelerometer use in children with idiopathic toe walking (ITW). Methods: Seventy-five children, 2 to 13 years old, with ITW were videotaped ambulating 50 ft wearing a NL-1000 accelerometer. Because of concerns for accelerometer accuracy in young children, 2 groups were created: 5 years or younger (n = 45) and 6 years or older (n = 30). Step counts recorded via accelerometer and video were compared and correlated. Results: There was a significant difference in accelerometer and video step counts for 2- to 5-year-olds ( W = 72.00, P < .001). No significant difference was found for 6- to 13-year-olds ( W = 65.00, P = .24). Spearman ρ values were 0.78 and 0.92 for the 5 years or younger and 6 years or older groups, respectively. Conclusion: Accelerometers accurately count steps in 6- to 13-year-olds with ITW but are inaccurate in 2- to 5-year-olds. Abstract : This paper assesses whether accelerometers accurately measure step count in children with idiopathic toe walking aged between 2-13 years compared to videotaped observations.